Mechanical Properties of Elastomeric Impression Materials: An In Vitro Comparison - Dino Re; Francesco De Angelis; Gabriele Augusti; Davide Augusti; Sergio Caputi; Maurizio D’Amario; Camillo D’Arcangelo (International Journal of Dentistry)
Purpose. Although new elastomeric impression materials have been introduced into the market, there are still insufficient data about their mechanical features. The tensile properties of 17 hydrophilic impression materials with different consistencies were compared. Materials and Methods. 12 vinylpolysiloxane, 2 polyether, and 3 hybrid vinylpolyether silicone-based impression materials were tested. For each material, 10 dumbbell-shaped specimens were fabricated (n=10), according to the ISO 37:2005 specifications, and loaded in tension until failure. Mean values for tensile strength, yield strength, strain at break, and strain at yield point were calculated. Data were statistically analyzed using one-way ANOVA and Tukey’s tests (α=0.05). Results. Vinylpolysiloxanes consistently showed higher tensile strength values than polyethers. Heavy-body materials showed higher tensile strength than the light bodies from the same manufacturer. Among the light bodies, the highest yield strength was achieved by the hybrid vinylpolyether silicone (2.70 MPa). Polyethers showed the lowest tensile (1.44 MPa) and yield (0.94 MPa) strengths, regardless of the viscosity. Conclusion. The choice of an impression material should be based on the specific physical behavior of the elastomer. The light-body vinylpolyether silicone showed high tensile strength, yield strength, and adequate strain at yield/brake; those features might help to reduce tearing phenomena in the thin interproximal and crevicular areas.